Diferensiasi Pengaturan Join Venture Agreement Terhadap Penanaman Modal Asing Sebagai Bentuk Perwujudan Ekonomi Berkelanjutan: The Impact of Differentiated Provisions in Joint Venture Agreements on Foreign Direct Investment as a Means of Achieving a Sustainable Economy - Muhammad Fadhil (SIYASI: Jurnal Trias Politica, 2023)
Legal protection provided by a country as a host country for investors in the business world is essential. Along with the rapid pace of economic turnover, discourse on foreign investment is increasingly in the spotlight considering the importance of investment in encouraging economic development for a country. But unfortunately, the ideal conditions are inversely proportional to the reality of the investment mechanism through the Join Venture Agreement. The problem that will be examined by the author is to focus on the incompatibility of the articles of association with the laws and regulations that have been applied in Indonesia. Moreover, another problem in the Join Venture mechanism in Indonesia is that there is regulatory differentiation with the implementation of joint ventures between foreign companies and local companies that can hamper the pace of the Indonesian economy. The role is so large related to investment for national development, it is natural that capital determination receives special attention from the government, especially presenting juridical efforts that can overcome investment problems in a country.